Do the various leisure forms have equal effects on mental health? A longitudinal analysis of self-selected leisure activities - Bian, Junyi; Xiang, Zubing (Frontiers in Public Health, 2023)
This study aimed to test whether engagement in different domains of leisure is associated with a composite index of mental health, concurrently and subsequently. Longitudinal data, including 10,968 participants with a mean age of 46.01 in the Chinese General Social Survey (CGSS), was analyzed using generalized estimating equations with a logit link. The results showed that face-to-face experiences, such as sport with all ORs < 1 at α = 0.01 significant level and meeting with all ORs < 1 at α = 0.01 significant level except daily meeting frequency in person, are important for protecting mental health due to increasing social support through building close ties. The results also indicate that online leisure with all ORs < 1 at α = 0.01 significant level affects positively on lowering odds of depression. In addition, receptive cognitive leisure, such as watching television or movies with all ORs < 1 are not significant at α = 0.05 level, was not consistently associated with depression, and active cognitive leisure, such as reading with all ORs < 1 at α = 0.01 significant level, was associated with lower odds of depression.